A mutation in the Neisseria gonorrhoeae rfaD homolog results in altered lipooligosaccharide expression. - Drazek, E S (1995)
The gonococcal lsi-6 locus was cloned and shown by DNA sequence analysis to have homology with the E. coli rfaD gene, which encodes ADP-L-glycero-D-mannoheptose epimerase. This enzyme is involved in the biosynthesis of the lipopolysaccharide precursor ADP-L-glycero-D-mannoheptose. A site-directed frameshift mutation in lsi-6 was constructed by PCR amplification and introduced into the chromosome of Neisseria gonorrhoeae MS11 P+ by transformation. The lipooligosaccharides (LOS) of mutant and parental strains were characterized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The lsi-6 mutant produced LOS components with apparent molecular masses of 2.6 and 3.6 kDa as compared with a 3.6-kDa band of the MS11 P+ strain. The parental LOS phenotype was expressed when a revertant was constructed by transformation of the cloned wild-type gene into the lsi-6 mutant. The immunoreactivity of LOS from parental and constructed strains was examined by SDS-PAGE and Western blotting. Only the parental and reconstructed wild-type strains produced a 3.6-kDa LOS component that reacted with monoclonal antibody 2-1-L8. These results suggest that the lsi-6 locus is involved in gonococcal LOS biosynthesis and that the nonreactive mutant 3.6-kDa LOS component contains a conformational change or altered saccharide composition that interferes with immunoreactivity.